1778 N.J. Laws 45, 2d. General Assembly, An Act for the Regulating, Training and Arraying of the Militia, ch. 21, § 11. - (:unkn) unknown (General Publisher, 1778)
That every Person enrolled shall constantly keep himself furnished with a good Musket, well fitted with a Bayonet, Steel Ramrod and Worm, a Cartridge-box, twenty three Rounds of Cartridges sized to his Musket, a Priming-wire, Brush and twelve Flints, a Knapsack and Canteen
--
Keywords: ARMED FORCES